Quantitative evaluation of the effects of positional versus orientational disorder on the scattering of acoustic phonons in disordered matter: Related Topics - Bermejo, F.J.; Fernández-Perea, R.; Cabrillo, C.; Krivchikov, A.I.; Yushchenko, A.N.; Manzhelii, V.G.; Korolyuk, O.A.; González, M.A.; Jimenez-Ruiz, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The phonon scattering processes in the three solid phases of ethanol are investigated using thermal conductivity,light, and neutron-scattering measurements as well as molecular dynamics simulations on single-crystalline models for two crystalline modifications (fully ordered monoclinic and orientationally disordered bcc phases). The orientationally disordered crystal is found to exhibit a temperature dependence of the thermal conductivity that is remarkably close to that of a structurally disordered solid, especially at low temperatures. This results, together with measurements of Brillouin linewidths as derived from light scatteringmeasurements, emphasize the role of orientational disorder in phonon scattering. The experimental results obtained on polycrystal samples are then discussed with the aid of computer simulations on single-crystalline models of both bcc and monoclinic crystals. Our findings are in good agreement with the wealth of thermodynamic and dynamic data available so far, but at variance with the inferences drawn from inelastic x-raydata on polycrystalline samples, where a common nature for the excitations in all phases is postulated.